Implementation Sharia Principles and Development of National Law In Sharia Share Trading In Indonesian Capital Market - Arsyad Aldyan (Activa Yuris: Jurnal Hukum, 2022)
In the capital market sector in Indonesia, especially with regard to stock trading in the capital market, sharia principles have begun to be applied properly. This is indicated by the existence of facilities (Sharia Online Trading System (SOTS) as well as brokers or securities companies that facilitate trading of shares in sharia, in addition to that added by the number of issuers listing sharia shares. Besides that, it is also supported more by the regulations issued by the national sharia board of the Indonesian Ulema Council and Otoritas Jasa Keuangan related to share trading in sharia. Finance as the institution tasked with overseeing the capital market. The National Sharia Council of MUI, issued regulations regarding sharia shares, among others, the Fatwa of the National Sharia Council No: 40/DSN-MUI/X/2003 concerning the Capital Market and General Guidelines for the Implementation of Sharia Principles in the Capital Market Sector; Fatwa of the National Sharia Council No: 80/DSN-MUI/III/2011 concerning the Implementation of Sharia Principles in the Mechanism of Trading in Equity Securities in the Regular Market of the Stock Exchange; while regarding sharia shares, Otoritas Jasa Keuangan issued the following regulations. Otoritas Jasa Keuangan Regulation No. 17/POJK.04/2015 concerning Issuance and Requirements for Sharia Securities in the Form of Shares by Sharia Issuers or Sharia Public Companies; Otoritas Jasa Keuangan Regulation No. 53 /POJK.04/2015 concerning Contracts Used in Issuing Sharia Securities in the Capital Market; Otoritas Jasa Keuangan Regulation No. 15/POJK.04/2015 Regarding the Implementation of Sharia Principles in the Capital Market